Community-Based Waste Management Strategy Through Self Governance Approach Towards a Healthy and Waste-Free Area in Deli Serdang Regency - Vera Asihna Riris Pasaribu; Dimpos Manalu (Jurnal Mamangan, 2025)
This study focuses on community-based waste management strategies in Deli Serdang Regency with a community self-help approach towards a healthy and waste-free area. The core problem raised in this study is the low level of community participation in waste management which has an impact on increasing the volume of unmanaged waste and has a negative impact on the environment and public health. The purpose of the study is to formulate an effective strategy to increase community awareness and participation in waste management, as well as build collaboration to realize a more efficient and sustainable waste management system. The method used in this study is a qualitative approach through participatory rural appraisal (PRA). Furthermore, data analysis was carried out by identifying key themes that emerged from the interaction, as well as developing a participatory strategy that involved the community in waste management. The results of the study indicate that the implementation of community-based waste management strategies through community self-help can increase community awareness and participation in waste management. It was found that effective counseling and training as well as the formation of community groups that focus on waste management have improved the community's ability to manage and recycle waste. In addition, the implications of this study also emphasize the importance of local government support in facilitating policies and providing the necessary infrastructure. The novelty of this study shows that community-based waste management strategies through independent governance have proven to be an effective alternative in creating healthy and waste-free areas in Deli Serdang Regency. This study is expected to be a reference for other regions in implementing similar programs to overcome waste problems at the community level